Case report: Novel variants cause developmental and epileptic encephalopathy in three unrelated families from Mali - Bamba, Salia; Sidibé, Lala; Diallo, Seybou H.; Cissé, Lassana; Dembélé, Kékouta; Yalcouyé, Abdoulaye; Ji, Weizhen; Dembélé, Mohamed Emile; Diarra, Salimata; Maiga, Alassane dit Baneye; Traoré, Oumou; Diallo, Salimata; et al. (Frontiers in Genetics, 2024)
Background and ObjectivesDevelopmental and epileptic encephalopathies (DEEs) are a group of neurological disorders characterized by early-onset seizures that are often resistant to treatment, by electroencephalographic abnormalities, and by developmental delay or regression. Their genetic basis remains largely unelucidated, especially in sub-Saharan Africa (SSA). We investigated the genetic bases of DEE in three Malian families.MethodsPatients underwent clinical evaluation, and DNA was obtained for whole exome sequencing (WES). Putative variants were screened in all available family members and in silico prediction analyses were performed to assess pathogenicity.ResultsFive patients from three unrelated families with DEEs had symptoms that started during the neonatal period with seizures and myoclonus that became refractory to antiepileptic medications. WES identified previously unreported variants in all three families: homozygous variants in GRIN1 and SYNJ1, and compound heterozygous variants in RARS2. These variants affected protein structure by in silico tools and were classified as variants of uncertain significance hot, pathogenic/likely pathogenic respectively according to ACMG criteria.DiscussionWe identified rare variants in three genes (GRIN1, SYNJ1, and RARS2) associated with early onset of DEEs in SSA, expanding their genetic and epidemiological spectrum. Larger cohort studies in SSA may unravel more variants with potential clinical implications and further our understanding of the disease mechanism.